2017
DOI: 10.1016/j.ribaf.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sanctions and the Russian stock market

Abstract: The article presents the robust estimates of extreme movements and heavy-tailedness properties for Russian stock indices returns before and after sanctions were introduced. The obtained results show that virtually for all sectoral indices there was a statistically significant increase in volatility. At the same time there is not enough evidence of structural breaks in heavy-tailedness, though some indications of a higher degree of heavy-tailedness of both right and left tails in the post-imposition period can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 48 publications
3
12
0
1
Order By: Relevance
“…The predicted impact of the sanctions on GDP was estimated at -2.4 percentage points by 2017 compared to the hypothetical scenario without sanctions, but this is 3.3 times lower than the estimated impact of the oil price shock. (Ankudinov et al, 2017) examined the impact of the sanctions on the Russian stock market. The results showed that for almost all industry indicators, a statistically significant increase in volatility was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted impact of the sanctions on GDP was estimated at -2.4 percentage points by 2017 compared to the hypothetical scenario without sanctions, but this is 3.3 times lower than the estimated impact of the oil price shock. (Ankudinov et al, 2017) examined the impact of the sanctions on the Russian stock market. The results showed that for almost all industry indicators, a statistically significant increase in volatility was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to study stock market volatility under sanctions, Goudarzi (2014) showed that the Iranian stock market has not been influenced by the sanctions. Furthermore, the results of Ankudinov et al (2017) indicated that for almost all sector indices of Russian market return, there was a statistically significant relationship between them and the imposed sanctions but it did not lead to a structural break. Garshasbi and Yousefi (2016) evaluated the effects of Iran sanctions on macroeconomic variables via indexing sanctions and found the direct impacts only on the economic growth rate.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Despite some earlier studies on the effects of external shocks on financial markets, such as Bancit et al (2016), Jin and An (2016), Castagneto-Gissey and Nivorozhkin (2016), Ankudinov et al (2017), Atkins et al (2018), Liu et al (2019), andSamadi et al (2021), this is the first study to consider and prioritize the impacts of COVID-19 on financial markets in developed and developing nations. To this end, we analyze the experts' opinions through an MCDM (Multi-Criteria Decision Making) approach, namely Analytic Hierarchy Process (AHP), and based on the empirical part, we recommend some policy implications to enable financial markets to recover, which means opportunities for countries to improve the progress of SDGs.…”
Section: Introductionmentioning
confidence: 92%